Association of depressive symptoms with chronic liver disease among middle-aged and older adults in China - Zeng, Jingke; Lai, Xiaohuan; Wang, Shuigen; Zeng, Dijing; Ye, Jiangmin; Huang, Chunhua; Liu, Minhua; Zhang, Wenjuan; Xu, Hui (Frontiers in Psychiatry, 2023)
The relationship between depressive symptoms and chronic liver disease (CLD) is still unclear. We aimed to determine whether depressive symptoms are associated with CLD in a large population sample.The data was from the China Health and Retirement Longitudinal Study (CHARLS), an ongoing nationally representative prospective cohort study.Depressive symptoms were assessed with the catchment-area epidemiology survey-depression (CES-D). CLD was identified by the patient's self-report about a physician's diagnosis at each visit. Multi-adjusted logistic regression and Cox regression models were used.Results: A total of 14995 participants (53.1% female; mean age: 58.85 ± 9.87 years) and 13405 participants (53.64% female; mean age: 58.58±9.69 years) were included in the cross-sectional and longitudinal analyses, respectively. In the cross-sectional analysis, the odds ratio of CLD in patients with moderate and severe depressive symptoms were 1.46 [ 95% confidence interval (CI), 1.16-1.83] and 1.78 (95% CI, 1.23-2.56) than those with none/mild depressive symptoms, respectively. In the longitudinal analysis, compared to participants with none/mild depressive symptoms, the hazard rates of CLD in those with moderate and severe depressive symptoms were 1.65 (95%CI, 1.33-2.03) and 1.80 (95%CI, 1.24-2.60). And the 50th percentile difference of time (years) at the incidence of CLD in participants with moderate and severe depressive symptoms were -0.83 (95%CI, -1.18, -0.49) and -0.96 (95%CI, -1.56, -0.35), respectively.Conclusions: Elevated depressive symptoms were associated with an increased risk of CLD among middle-aged and older adults in China.